Ekonomia kultury - przedmiot i główne problemy - Karaś-Doniec, Alicja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The article deals with the scope of surveys to-date on cultural economics as a recently established sub-discipline of economics. It provides explanations of definitions, lists the main goal of cultural economics and discusses some of its most intriguing aspects such as Baumol's cost disease, taste formation, public subsidies and the art market, all of which build a framework for the microeconomical characteristics of cultural economics. The characteristics provide a description of the circumstances in which individuals and organizations engage and carry out their activities in the field of culture, art, and heritage. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 73-83